Application of Granular Activated Carbon-Sequencing Batch Reactor (GAC-SBR) System for Treating Wastewater from Slaughterhouse - Sirianuntapiboon, Suntud; Manoonpong, Kwannate (Science & Technology Asia, 2015)
-